Gambaran Pengetahuan Pemulung Terhadap Limbah Medis Padat di TPA Suwung - Apriyanthi, D.P. Risky Vidika; Artini, Ni Putu Rahayu (Bali International Scientific Forum, 2020)
Background: The facilities and infrastructure of waste management in the city of Denpasar currently owned are not comparable to the abundant production of waste produced by the community, causing wild polling stations to appear everywhere, so that it has the potential to cause environmental pollution around polling stations. One type of waste that is prohibited from being disposed to landfill is the type of medical waste. On January 15, 2018 there were still solid medical waste dumped into the Suwung landfill.  Purpose: This study aims to determine the description of scavenger knowledge in the Suwung landfill on medical waste and its impact on health. Method: The research method used was a cross-sectional descriptive study. The research sample was taken by accidental sampling. Data was collected directly through informed consent and filling out questionnaires by respondents. Respondents in this study were 50 people who work as scavengers at the TPA Suwung. Result:  58 % of respondents did not know about medical waste, 80% of the respondents did not know the types of medical waste at the TPA Suwung. 58% of respondents did not know the impact of medical waste on health and 56% of respondents did not know that medical solid waste can cause disease. Conclusion: The knowledge of scavengers at the Suwung landfill on medical waste and its impact on health is still very low. the majority of respondents did not know the types of medical waste and their impact on health